(untitled) (Bangladesh Journal of Child Health, 2024)
Background: To assess neonatal mortality, many validated scores have been developed. The modified sick neonatal score (MSNS) is an easy, less complex suitable for both term and preterm neonates. This study was conducted to predict mortality upon admission to a NICU using the MSNS score. Methods: An observational study was conducted in the Department of Neonatology, BSMMU, Dhaka, over a period of one year. Parameters for MSNS score were collected from data sheet. Outcome expressed as survived or expired. All data were analyzed using SPSS 20. To determine the cutoff value for predicting mortality, a receiver operating curve was generated. The cutoff score’s sensitivity, specificity, positive predictive value, and negative predictive value were calculated. Results: Among the enrolled 114 neonates, mean gestational age and mean birth weight were 34.22±3.10 weeks and 1967.87±752.33g respectively. About 75.4% neonates were <2500 grams and 70.2% of babies were preterm. During the study period, two third (69.3%) baby survived. The mean MSNS among survived neonate was 11.77± 2.29 and in expired neonates was 9.66±2.32 which was statistically significant (p-<0.01). The area under the ROC curve was 0.740 (95% CI: 0.645- 0.835). The optimal cutoff value obtained to predict mortality was 11.50. With this cutoff score the sensitivity and specificity were 80% and 58%. Positive predictive value and negative predictive value were 46% and 87% respectively. Conclusions: MSNS tools can be used to predict early mortality with early referrals and prompt treatment to reduce neonatal mortality. Bangladesh J Child Health 2023; Vol 47 (2) : 72-77